HISTOPATHOLOGICAL STUDY OF SALIVARY GLAND LESIONS IN A TERTIARY CARE CENTRE - Dr. Sheela Lakshamanrao Gaikwad; Dr. Sneha Sadashiv Sulkar; Dr. Nitin Gautam Kamble; Dr. Arvind Namdeorao Bagate (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: Between 3–10% of tumors are salivary gland neoplasms, which are uncommon malignancies. Although immunohistochemistry (IHC) advancements have recently contributed significantly to improving the accuracy of the identification of these cancers, hematoxylin and eosin (H&E) are still widely regarded as the best diagnosis method for salivary gland malignancies. Examining the histology of salivary gland lesions in a tertiary care facility was the aim of the study. Aims: To study the incidence, age at occurrence, and sex ratio of individuals with salivary gland lesions, to record the range of lesions that affect the salivary glands as well as their frequency. Setting and Designs: This was the prospective study on salivary gland lesions that was carried out from January 1, 2021, to June 30, 2022, for a period of 18 months. Result: From the 35 cases that were encountered for the current investigation, 18 (70.1%) were benign, 14 (41.1%) were inflammatory, and the final 3 (41.8%) were malignant. The most commonly affected salivary gland in the present study was the parotid. The more prevalent lesions were benign, followed by malignant lesions. Conclusion: Because of the COVID-19 pandemic’s restricted availability of cases, this study was unable to include some tumor types, such as acinic cell carcinomas, because of their exceedingly uncommon occurrence. Therefore, we suggest additional research.